How to predict good days in farming: ethnomathematics study with an ethnomodelling approach - Umbara, Uba; Wahyudin, Wahyudin; Prabawanto, Sufyani (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2021)
Mathematics cannot be separated from everyday life. The use of mathematical concepts in cultural activities can be studied through the ethnomathematics program. However, ethnomathematics research may not be able to provide noticeable results, especially in constructing mathematical modelling for pedagogical purposes. Ethnomodelling later became one of the concepts introduced as an approach in ethnomathematics research. Based on the cultural aspect, the ability to predict a good day in farming is included in the holistic concept of culture because it belongs to the knowledge system and belief system (religion) in the universal element of culture. The research was conducted using an ethnomethodological approach and a realist ethnographic design. Based on this, this research was conducted to describe the ability of the Cigugur indigenous people in Kuningan Regency to predict what days are considered good to start farming activities. Data were collected by using observation techniques, in-depth interviews, documentation, and field notes. Data analysis techniques are carried out in stages through content analysis, triangulation, and pattern search. Based on the study of ethnomathematics, research that is able to describe the mathematical ideas and practices of the indigenous Cigugur community can be classified into several fundamental mathematical dimensions including counting, finding, measuring, designing, and explaining. The use of the ethnomodelling approach in research can describe several mathematical concepts used by the concepts of numbers, sets, relations, congruence, modulo, and mathematical modelling.